Characterization of the Snow Mountain agent of viral gastroenteritis. - Madore, H P (1986)
Snow Mountain agent (SMA) is a 27- to 32-nm virus which is the etiologic agent of outbreaks of acute gastroenteritis in Colorado and Vermont. SMA is morphologically similar to but antigenically distinct from the Norwalk and Hawaii agents of viral gastroenteritis but, like those agents, has not been cultivated in vitro. We purified and characterized SMA directly from human stool specimens containing the virus. The density of the SMA virion was 1.29 g/cm3 and 1.21 to 1.22 g/cm3 on potassium tartrate-glycerol gradients and 1.33 to 1.34 g/cm3 on cesium chloride gradients. SMA had an S value of 170 to 183S on a sucrose velocity gradient. The purified virion was iodinated, immunoprecipitated with acute and convalescent sera from volunteers challenged with SMA, and analyzed on polyacrylamide gels. The virion contains one major structural protein of 62,000 molecular weight, which is similar in size to the 59,000-molecular-weight protein found in the Norwalk virion. The biophysical properties and single structural protein of SMA most closely resemble those of the calicivirus group.